2020
DOI: 10.3389/fcell.2019.00375
|View full text |Cite
|
Sign up to set email alerts
|

ERas Enhances Resistance to Cisplatin-Induced Apoptosis by Suppressing Autophagy in Gastric Cancer Cell

Abstract: Gastric cancer (GC), a common type of malignant cancer, remains the fifth most frequently diagnosed cancer and the third leading cause of cancer-related deaths worldwide. Despite developments in the treatment of GC, the prognosis remains poor. Embryonic stem cell-expressed Ras (ERas), a novel member of the Ras protein family, has recently been identified as an oncogene involved in the tumorigenic growth of embryonic stem cells. A recent study reported that ERas is expressed in most GC cell lines and GC specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Autophagy has been suggested to play controversial roles in cancer therapy. In some cases, autophagy is confirmed to have cytoprotective effects on the survival of cancer cells, and autophagy inhibition could potentiate the sensitivity of cancer cells to anticancer drugs, such as cisplatin and doxorubicin (Li et al, 2017;Xu et al, 2017;Tian et al, 2019). However, more evidences reveal that autophagy activation could promote cancer cell death (Denton and Kumar, 2019;Kriel and Loos, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been suggested to play controversial roles in cancer therapy. In some cases, autophagy is confirmed to have cytoprotective effects on the survival of cancer cells, and autophagy inhibition could potentiate the sensitivity of cancer cells to anticancer drugs, such as cisplatin and doxorubicin (Li et al, 2017;Xu et al, 2017;Tian et al, 2019). However, more evidences reveal that autophagy activation could promote cancer cell death (Denton and Kumar, 2019;Kriel and Loos, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after this treatment, an increase in astrocytic (GFAP; Glial Fibrillary Acidic Protein) and neuronal (TUBB3; Tubulin Beta 3 class III) differentiation markers in GSCs was revealed. This autophagy-mediated differentiation has been highlighted in some other cancer types, including colon, liver and gastric cancers [81][82][83]. A 2019 study [84] demonstrated both in vitro and in vivo that metformin, a common drug used to treat type II diabetes, could suppress the self-renewal and tumorigenicity abilities of Osteosarcoma Stem Cells (OSCs).…”
Section: Rab Family Autophagy and Cscsmentioning
confidence: 99%
“…Embryonic stem cell-expressed Ras (ERas) is a novel member of the Ras protein family and is highly expressed in gastric, colorectal, and breast cancer ( SuĂĄrez-Cabrera et al, 2018 ; Tian et al, 2019 ). Tian et al (2019) have found that ERas overexpression significantly increases the phosphorylation level of mTOR (Ser2448) and its substrate (ULK1-Ser757), as well as AKT-Ser473, activates the AKT/mTOR pathway, blocks autophagic flux in gastric cancer cells, suppresses DDP-induced apoptosis, and induces DDP resistance. In contrast, silencing ERas has been found to increase autophagic flux and enhance the sensitivity of gastric cancer cells to DDP in vitro ( Tian et al, 2019 ).…”
Section: Dual Roles Of Autophagy In Chemoresistance Of Gastric Cancermentioning
confidence: 99%